Desenvolvimento de um sistema microcontrolado para a coleta da temperatura do solo - Costa, Erasmo (2022)
This work presents the study, development and physical implementation of microcontrolled device, projected to collect soil microclimate (temperature) data. Considering that various climate changes that occur in the planet, tht divergency about microclimate studies and the atmosphere temperetured collected and, also, the great difficult to realize studies about these theme, the project searches about the development of a device capable of mesure soil temperature, in an authonomous way, for certains periods of time. Using a PIC microcontroller (PIC16F877A), temperature sensors (DS7505U+), EEPROM memory (AT24C256), serial interface (FT232RL) and lithium batteries (SD18650), it is fulfilled a detailed study of the componentes used, analyzing its maily characteristics and justifying its use. The development, simulation, construction and testing are explained and justified trying to get the best performance in the data collecting, in a compact, and, at the same time, robust and eficiente system. The developed device achieve all the features citted and also surprise cosuming less current than the foreseen.